ความชุกของการทดสอบการแพ้ยาโดยการให้รับประทานยาแล้วให้ผลลบในการวินิจฉัยผู้ที่มีผื่นแพ้ยาปฏิชีวนะกลุ่มไม่ใช่เบต้าแลคแตมแบบไม่เฉียบพลันที่มีผลการทดสอบการแพ้ยาทางผิวหนังด้วยวิธีการฉีดเข้าในชั้นผิวหนังและการตรวจไซโตไคน์อินเตอร์เฟอรอนแกมมาที่หลั่งจากเม็ดเลือดขาวที่มีความจำเพาะกับยาในเลือดโดยวิธีอิไลสปอตให้ผลลบ - นฤมล รัตนสุธีรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Background: Non-betalactam antibiotics are increasingly prescribed nowadays resulting in increasing numbers of patients suspected of non-betalactam allergy. Currently, there is no practical method available to diagnose non-betalactam antibiotics hypersensitivity. Objective: To evaluate the negative predictive value of intradermal test (IDT) and interferon-gamma (IFN-γ) enzyme-linked immunospot (ELISpot) assay in patients with NI and non-severe cutaneous adverse reactions to non-betalactam antibiotics: cotrimoxazole, macrolides, quinolones, clindamycin, and metronidazole.Materials and Methods: IDT and ELISpot assay were performed in 26 patients. 20 drug provocation tests were performed in 19 patients with combined negative IDT and ELISpot.Results: The study showed positive results by ELISpot in 4 patients (4/10, 40%) while one positive result to the IDT (1/10, 10%). Nineteen patients with combined negative results to both tests underwent the drug provocation test. The provocation test revealed 5 positivity; 3 with fixed drug eruption and 2 with maculopapular exanthema. The combined positive rate of IDT and ELISpot test was 50% (5/10) and negative predictive value of the tests was 75. Conclusion: The combination of IDT, ELISpot and drug provocation test should be considered to aid in the diagnosis of NI hypersensitivity reactions to non-betalactam antibiotics.